Synthesis and Characterization of Hematite (α-Fe₂O₃) Nanomaterials from Red Mud Using EDTA as Capping Agent - Berlian Sitorus; Yunior Arta Arga Manulang; Risya Sasri; Seno D. Panjaitan (Jurnal Kimia Sains dan Aplikasi, 2025)
Hematite (α-Fe2O3) nanomaterials, a stable phase of iron oxide, hold significant potential for diverse materials science and technology applications. In this study, red mud was employed as a low-cost precursor for synthesizing hematite nanomaterials, with ethylenediaminetetraacetic acid (EDTA) used as a capping agent to prevent particle agglomeration. The effect of EDTA on particle size and colloidal stability was investigated by comparing three synthesis variations: (a) without EDTA (NPH-1), (b) with EDTA via the precipitation method (NPH-2), and (c) with EDTA via the hydrothermal method (NPH-3). XRD analysis confirmed the formation of crystalline hematite (α-Fe2O3) in all samples. FT-IR spectroscopy revealed absorption bands at 1624 cm−1 and 1382 cm−1, corresponding to the symmetric and asymmetric stretching vibrations of the carboxylate (COO−) group, respectively. The difference in these wavenumbers suggests monodentate coordination between the carboxyl groups of EDTA and the hematite nanoparticle surfaces. Particle size analysis indicated that the EDTA-assisted synthesis via precipitation (NPH-2) produced the smallest average particle size (149.6 nm) with a narrow size distribution, as reflected by a polydispersity index (PDI) of 0.43. Furthermore, this sample demonstrated enhanced colloidal stability with a zeta potential of −34.0 mV. These findings suggest that the synthesized α-Fe2O3 nanomaterials produced with narrow particle size distribution and high colloidal stability, are promising for visible-light photocatalysis.